2021
DOI: 10.1186/s41936-021-00226-x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the geographic distribution habitats of Schizomyia buboniae (Diptera: Cecidomyiidae) and its host plant Deverra tortuosa (Apiaceae) in Egypt by using MaxEnt modeling

Abstract: Background In some localities of the Mediterranean coast and the Nile land region, the gall midge Schizomyia buboniae Frauenfeld, 1859 (Diptera: Cecidomyiidae) induce small barrel-shaped galls on the stem of Deverra tortuosa (Desf.) DC. (Family: Apiaceae). Host plants interact with several insects in a different manner. The current work studies the interaction of S. buboniae with D. tortuosa. Furthermore, the present work predicted the distribution of S. buboniae and its host plant D. tortuosa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
2
2
0
Order By: Relevance
“…The present study showed that max temperature of the warmest month, isothermality, and precipitation of the coldest quarter were the most important predictors of S. botellus habitat distribution. This agrees with the findings of (Blanche andLudwig, 2001, andKamel et al, 2021) who reported that gall-making insects show increases in performance at higher mean temperatures. Additionally, (Ragab et al, 2020a) showed that precipitation in the coldest quarter was one of the most important predictors of Baldratia salicorniae habitat distribution.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present study showed that max temperature of the warmest month, isothermality, and precipitation of the coldest quarter were the most important predictors of S. botellus habitat distribution. This agrees with the findings of (Blanche andLudwig, 2001, andKamel et al, 2021) who reported that gall-making insects show increases in performance at higher mean temperatures. Additionally, (Ragab et al, 2020a) showed that precipitation in the coldest quarter was one of the most important predictors of Baldratia salicorniae habitat distribution.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, the present study showed that the axillary buds of D. triradiata are facing gall induction by S. botellus. While the gall midge Schizomyia buboniae is inducing gall on the stem of Deverra tortuosa (Kamel et al, 2021). The present study showed that max temperature of the warmest month, isothermality, and precipitation of the coldest quarter were the most important predictors of S. botellus habitat distribution.…”
Section: Discussionsupporting
confidence: 47%
“…The MaxEnt model can complete the simulation analysis of the suitable area of RWW under current and future climatic conditions, and the prediction results are stable, reliable, and easy to interpret. It has been widely applied to various species [48,49]. However, the default parameters of the MaxEnt model were predominantly used in previous studies, which could lead to excessive model fitting [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…Parapodia sinaica insect (Lepidoptera: Gelechiidae), induces a spindle gall on the stem of Tamarix. (Fusu, 2017p Bidzilya et al, 2019Kamel et al, 2021 ;Baugnée et al, 2022). For the first time, P. sinaica (the host of T. tamaricis sp.)…”
Section: Introductionmentioning
confidence: 99%